The Use of Fly Ash in Peat Soil on the Growth and Yield of Rice - Nelvia Nelvia (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
The research aims to study the use of fly ash for improving the growth and yield of rice in peatland. The peat soil material that used in this study was sapric weathering level. The field research was designed by using a completely randomized design. The treatment in this study was the application of fly ash consisting of six levels (0, 25, 50, 75, 100 and 125 g fly ash per pot), each treatment repeated 4 times. The results showed that the best plant growth and yield of rice were gained from the application of fly ash at the lower dose (25 g pot-1 and 75 g pot-1, respectively). The increase in fly ash dose (100 g pot-1 and 125 g pot-1) did not gave the highest rice yield (9.67% and 0.2% lower than the dose of 75 g pot-1) due to the macronutrients N, P and K as a limiting factor (only as a basic fertilizer).